Disability as a Philosophical Problem: Deficient Thinking and Its Instituting Power in the School Institution - Pagni, Pedro Angelo [UNESP] (Univ Estadual Ceara-uece, 2024)
This essay discusses disability as a philosophical problem. It frames the perspective of its enunciation as a response to its partial interdiction as a problematic field in Philosophy and Education, aiming to question to what extent these areas, by ignoring it, have revealed their own deficiencies. It draws on the philosophies of difference, in sync with Nietzschean and Spinozan traditions, to propose this enunciation and provocatively attempt to answer this inquiry. It suggests that there is a philosophy of disability that challenges inclusive education today, due to its instituting power within the school institution.
Keywords: disability; philosophical problem; inclusive education; philosophies of difference